(NfIZI^ESKAQ AKUSTIKA KRISTALLOW (B/s - (NbARANSKIJ(B, (NkONSTANTIN nIKOLAEWI^s ((NmOSKWA (B:s (Nmgu(B,s, 1991)
(NbIBLIOGR(B.: (NS(B. 142-143 (59 (NNAZW(B.)s
Keywords: (NzWUKOWYE WOLNYs; (NaKUSTIKA KRISTALLOWs; (NkRISTALLYs; (NrASPROSTRANENIE W KRISTALLAHs